Bending Behaviour Of Triangular Web Profile Steel Beam Section - Hashim, Nor Salwani (2012)
Corrugated beams and girders are widely used in industrial buildings, warehouses or in bridge constructions for road and rail. In order to assure that the steel section can resist more loads compared to that of flat web steel section (FW), a new steel section known as triangular web profile (TRIWP) steel section has been studied. A TRIWP steel section is a built-up steel section consisting of two flanges connected to a web plate with a triangular profile. This thesis described the study on the bending behaviour about major (Ix) and minor (Iy) axes of TRIWP compared to that of flat web (FW) steel sections. This research consists of two main stages namely finite element analysis and laboratory testing.